COVID-19 impacts equine welfare: Policy implications for laminitis and obesity. - Ashley B Ward; Kate Stephen; Caroline McGregor Argo; Patricia A Harris; Christine A Watson; Madalina Neacsu; Wendy Russell; Dai H Grove-White; Philippa K Morrison (PLoS ONE)
The COVID-19 pandemic continues to impact human health and welfare on a global level. In March 2020, stringent national restrictions were enforced in the UK to protect public health and slow the spread of the SARS-CoV-2 virus. Restrictions were likely to have resulted in collateral consequences for the health and welfare of horses and ponies, especially those at risk of obesity and laminitis and this issue warranted more detailed exploration. The current study utilised qualitative methodology to investigate the implications of COVID-19 related policies upon equine management and welfare with a focus on horses and ponies at risk of laminitis and obesity. Twenty-four interviews with five sub-groups of key equestrian welfare stakeholders in the UK were conducted between May and July of 2020 to understand the challenges facing equine welfare in the context of laminitis and obesity susceptible animals. Thematic analysis revealed lockdown-associated factors with the potential to compromise welfare of horses and ponies at risk of obesity and laminitis. These included: disparate information and guidance, difficulties enacting public health measures in yard environments, and horses having reduced exercise during the pandemic. Positive examples of clear and consistent information sharing by farriers were reported to have improved horse owner understanding of routine hoof care during lockdown. Analysis suggested that the recommendations for supporting the management-based needs of horses under reduced supervision were not clearly defined, or were not sufficiently disseminated, across the equine industry. These findings support the development of guidelines specific to the care of horses and ponies at risk of obesity and laminitis through collaborative input from veterinary and welfare experts, to reduce the negative impacts of future lockdown events in the UK.